Comparing the Outcomes of the Different Teaching Modes: All-in-Person, Hybrid, and Online, for Different Student Demographic Groups in a Business School - Moodie, Douglas Rome (Online Learning, 2021)
The concept of hybrid education is spreading. Far less research has been done comparing hybrid teaching to online and F2F teaching. Nearly all this research assumes that there is no difference in the students entering F2F, Hybrid, or online sections of a course. This study used data from four years of courses that were taught in Coles College of Business at Kennesaw State University. This data set with individual student and course outcomes, included full student demographics including previous university GPA. The results showed for all demographics, hybrid course sections gave better final course grades than online sections, which in gave better final grades than F2F sections. However, for instructors who taught Hybrid courses also gave higher course GPAs for F2F sections than those who did not teach hybrid.